Applications of Microbial Enzymes in Food Industry - Raveendran, Sindhu; Parameswaran, Binod; Ummalyma, Sabeela Beevi; Abraham, Amith; Mathew, Anil Kuruvilla; Madhavan, Aravind; Rebello, Sharrel; Pandey, Ashok (Food technology and biotechnology, 2018)
The use of enzymes or microorganisms in food preparations is an age-old process. With the advancement of technology, novel enzymes with wide range of applications and specificity have been developed and new application areas are still being explored. Microorganisms such as bacteria, yeast and fungi and their enzymes are widely used in several food preparations for improving the taste and texture and they offer huge economic benefits to industries. Microbial enzymes are the preferred source to plants or animals due to several advantages such as easy, cost-effective and consistent production. The present review discusses the recent advancement in enzyme technology for food industries. A comprehensive list of enzymes used in food processing, the microbial source of these enzymes and the wide range of their application are discussed.